Letramento visual : trabalhando a fotografia documental no ambiente escolar - Andrade, Cynthia Carlla de Almeida (2015)
Currently, despite the iconographic language be disseminated through images, students in all segments are struggling to read, interpret and correlate images, especially photography, which are constantly used in textbooks, newspapers and magazines printed or virtual. The documentary photography in addition to register important historical moments provides the critical reflection of what is recorded. In this way, it was elaborated and applied a didactic project with students of the 9th year of School Unit Municipal School of Swallow in order to provide visual literacy from documentary photographic images. It was chosen as corpus of research some images/photos of photographer Sebastião Salgado for his work to prioritize a reflection about social ills. The research is based from the grammar of Visual Design of Kress and van Leween (1996) that lists aspects of an image that can be analyzed carefully. Was also of fundamental importance the gender studies of Baktin (2011), Marchuschi (2008), Dionysus (2011), among others. Given this, the present research was used in the first moment of a bibliographical research in order to provide justification for consistent, especially in relation to the semiotic studies with knowledge and deepening of the grammar of visual design (GDV) so that it could analyze the photographs chosen semiologicamente. The second step took place through action research, i.e. the analysis done in the light of the theory was put into practice through the application of lesson plans arranged in a didactic project, which culminated in a pedagogical sketchbook containing simplified explanations regarding GDV and the pedagogical project step-by-step with guidelines for the teacher.